Anticipating actions and corticospinal excitability: A preregistered motor TMS experiment. (September 2018) - Genschow, Oliver; Bardi, Lara; Brass, Marcel
Abstract: Past research on action observation and imitation suggests that observing a movement activates a corresponding motor representation in the observer. However, recent research suggests that individuals may not only reflexively simulate the observed behavior but also simulate and engage in anticipated action without another person actually engaging in it. For example, it has been demonstrated that observing a triggering event (i.e., nose wrinkling) that potentially leads to the anticipation of an action (i.e., nose scratching) increases the likelihood that the observer will perform that action. In the present research, we applied motor Transcranial Magnetic Stimulation (TMS) to investigate such anticipated social action effects at the neurophysiological level within a trial-by-trial measure. While a pilot study suggests that observing nose wrinkling elicits stronger motor evoked potentials (MEPs) in participants' biceps muscles than observing control events, this effect could not be fully replicated in a preregistered study. Although a post hoc meta-analysis across both studies supports the general hypothesis, these results need to be taken cautiously. Implications of the results reported in the manuscript are discussed.